THE IMPACT OF LANGUAGE LEARNING APPS ON ENGLISH PROFICIENCY - Mamadiyorova Sevara Olimjon's daughter (European Science Publishing, 2024)
This thesis examines the role of language learning applications in improving English proficiency, analyzing their effectiveness, limitations, and overall contribution to the language acquisition process. With the growing availability of mobile apps such as Duolingo, Babbel, and Rosetta Stone, English learners now have access to flexible, personalized, and engaging platforms that can supplement traditional learning methods. Through a combination of qualitative and quantitative research, this study explores how these apps support learners in achieving English proficiency while identifying key areas where they fall short. Ultimately, the findings suggest that language learning apps play a significant but supplementary role in language acquisition, particularly when combined with immersive and conversational learning methods.
Keywords: Language learning apps, english proficiency, mobile-assisted language learning (mall), duolingo, babbel, gamification in education, personalized learning, adaptive learning algorithms, vocabulary acquisition, grammar improvement, pronunciation practice, conversational fluency, speech recognition technology, english language education, educational technology.